Pengaruh Lingkungan Kerja dan Komunikasi terhadap Kepuasan Kerja Karyawan di Bank BJB Kantor Cabang Majalaya - Agi Dicko Permadi; Santi Wiranti (Jurnal Dimamu, 2022)
Based on the results of observations that underlie this research is the fluctuating number of employees at Bank BJB KC Majalaya. This encourages knowing the factors of the work environment and communication related to employee job satisfaction. This study aims to determine the effect of the work environment and communication on employee job satisfaction either partially or simultaneously at Bank BJB KC Majalaya. The object of research is the employees of Bank BJB KC Majalaya with a focus on aspects of the work environment, communication, and employee job satisfaction. This type of research is quantitative associative, the type of data is primary data and uses data collection techniques in the form of observations, interviews, questionnaires and literature studies. The population is 60 with the determination of the sample using the Slovin formula as many as 38 people. The results of this study indicate that the work environment has no effect on employee job satisfaction of 5.4% or tcount < ttable (1,439 < 1,689), communication has an effect on employee job satisfaction of 11,9 % or tcount > ttable (2,207 > 1,689) and simultaneously the work environment and communication have an effect on employee job satisfaction at Bank BJB KC Majalaya, which is 14.5% with F test results where count > Ftable (2,963 > 2.46).